2021
DOI: 10.1136/bmjopen-2020-045841
|View full text |Cite
|
Sign up to set email alerts
|

Exploring pain interference with motor skill learning in humans: a protocol for a systematic review

Abstract: IntroductionMotor skill learning is intrinsic to living. Pain demands attention and may disrupt non-pain-related goals such as learning new motor skills. Although rehabilitation approaches have used motor skill learning for individuals in pain, there is uncertainty on the impact of pain on learning motor skills.Methods and analysisThe protocol of this systematic review has been designed and is reported in accordance with criteria set out by the Preferred Reporting Items for Systematic Review and Meta-Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In order to evaluate the quality of evidence, the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach will be used 55. The GRADE approach supports reporting on both the size of the effect and certainty of evidence 56. Reporting will use statements recommended by the GRADE working group 57.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the quality of evidence, the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach will be used 55. The GRADE approach supports reporting on both the size of the effect and certainty of evidence 56. Reporting will use statements recommended by the GRADE working group 57.…”
Section: Methodsmentioning
confidence: 99%
“… 55 The GRADE approach supports reporting on both the size of the effect and certainty of evidence. 56 Reporting will use statements recommended by the GRADE working group. 57 The size of effect will be reported using four categories: large effect; moderate effect; small important effect; and trivial, small unimportant effect or no effect.…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review followed a pre-defined published protocol [ 24 ] and is reported in concordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) [ 25 , 26 ]. The protocol was registered on PROSPERO (CRD42020213240) on 15th October 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The eligibility criteria followed the PICOS framework and will be discussed briefly here; further details on inclusion and exclusion of studies are described in the protocol [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation